Upaya Peningkatan Kinerja Tenaga Kerja Bongkar Muat di Pelabuhan Marunda Jakarta Utara - Siti Krisnawati; Sugandi Sugandi; Gena Bijaksana (Institut Transportasi dan Logistik Trisakti, 2019)
The purpose of this research is to find out and analyze the suitability of loading and unloading performance in Marunda Port with existing regulation, human resource competence in using the equipment as well as condition of port facility used to load and unload at Marunda Port. Using qualitative approach with descriptive analysis, data was collected through documentation study method and in-depth interview, then analyzed. The result of the analysis shows that the conformity of loading and unloading performance in Marunda Port with the existing regulation is not optimal because of internal factors of TKBM and external factors of TKBM. While the competence of human resources in using the equipment in Port Marunda is not suitable to produce smoothness, speed and safety performance of loading and unloading goods from and to the ship docked at Marunda Port. Other resultshows that Marunda Port facilities and infrastructures still require improvements in order to obtain smoothness, speed and safety in the loading and unloading of goods from and ship at Marunda Port.